Religious Attendance in a Secular Country Protects Adolescents from Health-Risk Behavior Only in Combination with Participation in Church Activities - Buchtova, Marie; Malinakova, Klara; Kosarkova, Alice; Husek, Vit; van Dijk, Jitse P; Tavel, Peter (International journal of environmental research and public health, 2020)
Religiosity and spirituality have been considered to be protective factors of adolescent health-risk behavior (HRB). The aim of this study was to assess the relationship between adolescents' HRB and their religiosity, taking into account their parents' faith and their own participation in church activities. A nationally representative sample (n = 13377, 13.5 ± 1.7 years, 49.1% boys) of Czech adolescents participated in the 2018 Health Behavior in School-aged Children cross-sectional study. We measured religious attendance (RA), faith importance (FI) (both of respondents and their parents), participation in church activities and adolescent HRB (tobacco, alcohol, and cannabis use and early sexual intercourse). We found that neither RA nor FI of participants or their parents had a significant effect on adolescents' HRB. Compared to attending respondents who participate in church activities (AP), non-attending respondents who participate in church activities were more likely to report smoking and early sexual intercourse, with odds ratios (ORs) ranging from 3.14 (1.54-6.39) to 3.82 (1.99-7.35). Compared to AP, non-attending respondents who did not participate in church activities were more likely to report early sexual intercourse, with OR = 1.90 (1.14-3.17). Thus, our findings show that RA does not protect adolescents from HRB; they suggest that RA protects adolescents from HRB only in combination with participation in church activities.
Keywords: riskování; Adolescent Behavior; Spirituality; Cross-Sectional Studies; spiritualita; Adolescent; Child; zdravotně rizikové chování; HBSC study; dítě; Religion; adolescents; mladiství; spirituality; náboženství; Health Risk Behaviors; lidé; Risk-Taking; Humans; health-risk behavior; Sexual Behavior; sexuální chování; průřezové studie; religiosity; chování mladistvých